The role of environment on quenching, star formation and AGN activity. Issue Volume 15:Issue S359(2020) (March 2019) - Poggianti, Bianca M.; Bellhouse, Callum; Deb, Tirna; Franchetto, Andrea; Fritz, Jacopo; George, Koshy; Gullieuszik, Marco; Jaffé, Yara; Moretti, Alessia; Mueller, Ancla; Radovich, Mario; Ramatsoku, Mpati; et al.
Abstract: Galaxies undergoing ram pressure stripping in clusters are an excellent opportunity to study the effects of environment on both the AGN and the star formation activity. We report here on the most recent results from the GASP survey. We discuss the AGN-ram pressure stripping connection and some evidence for AGN feedback in stripped galaxies. We then focus on the star formation activity, both in the disks and the tails of these galaxies, and conclude drawing a picture of the relation between multi-phase gas and star formation.